Association of the alcohol dehydrogenase gene polymorphism rs1789891 with gray matter brain volume, alcohol consumption, alcohol craving and relapse risk. (23rd October 2017) - Bach, Patrick; Zois, Evangelos; Vollstädt‐Klein, Sabine; Kirsch, Martina; Hoffmann, Sabine; Jorde, Anne; Frank, Josef; Charlet, Katrin; Treutlein, Jens; Beck, Anne; Heinz, Andreas; Walter, Henrik; et al.
Abstract: Alcohol metabolizing enzymes, such as the alcohol dehydrogenases and the aldehyde dehydrogenases, regulate the levels of acetaldehyde in the blood and play an important role in the development and maintenance of alcohol addiction. Recent genome‐wide systematic searches found associations between a single nucleotide polymorphism (rs1789891, risk allele: A, protective allele: C) in the alcohol dehydrogenase gene cluster and the risk of alcohol dependence. The current study investigated the effect of this single nucleotide polymorphism on alcohol consumption, craving for alcohol, relapse risk and brain gray matter volume. Alcohol‐dependent patients ( n = 74) and controls ( n = 43) were screened, genotyped and underwent magnetic resonance imaging scanning, and relapse data were collected during 3 months following the experiment. Alcohol‐dependent A allele carriers reported increased alcohol craving and higher alcohol consumption compared with the group of alcohol‐dependent individuals homozygous for the C allele, which displayed craving values similar to the control group. Further, follow‐up data indicated that A allele carriers relapsed earlier to heavy drinking compared with individuals with two C alleles. Analyses of gray matter volume indicated a significant genotype difference in the patient group: individuals with two C alleles had reduced gray matter volume in the left and right superior, middle and inferior temporal gyri. Findings of the current study further support the relevance of genetic variants in alcohol metabolizing enzymes to addictive behavior, brain tissue volume and relapse risk. Genotype‐dependent differences in acetaldehyde formation, implicated by earlier studies, might be the biological substrate of the genotype differences. Abstract : This study presents initial evidence that a genetic polymorphism in the alcohol dehydrogenase gene cluster (rs1789891), which was associated with alcohol dependence risk before, is associated with increased alcohol cue‐induced craving, higher alcohol consumption, gray matter volume loss in bilateral temporal gyri and higher relapse risk in alcohol dependent patients.